2016
DOI: 10.1038/bjc.2016.111
|View full text |Cite
|
Sign up to set email alerts
|

Targeting cell death signalling in cancer: minimising ‘Collateral damage’

Abstract: Targeting apoptosis for the treatment of cancer has become an increasingly attractive strategy, with agents in development to trigger extrinsic apoptosis via TRAIL signalling, or to prevent the anti-apoptotic activity of BCL-2 proteins or inhibitor of apoptosis (IAP) proteins. Although the evasion of apoptosis is one of the hallmarks of cancer, many cancers have intact apoptotic signalling pathways, which if unblocked could efficiently kill cancerous cells. However, it is becoming increasing clear that without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 53 publications
(58 reference statements)
0
48
0
2
Order By: Relevance
“…2B and C). It has been confirmed that apoptosis could be induced through an intrinsic or extrinsic pathway (30)(31)(32), and activation of the caspase cascade was also involved in apoptosis (33). Only when caspase is cleaved can the activation of caspase occur.…”
Section: Discussionmentioning
confidence: 92%
“…2B and C). It has been confirmed that apoptosis could be induced through an intrinsic or extrinsic pathway (30)(31)(32), and activation of the caspase cascade was also involved in apoptosis (33). Only when caspase is cleaved can the activation of caspase occur.…”
Section: Discussionmentioning
confidence: 92%
“…Jest to możliwe dzięki wydzielaniu proapo-effectiveness of current therapies. This is possible due to the extrinsic induction of apoptosis by TRAIL signalling or inhibition of the antiapoptotic activity of Bcl-2 protein or IAP protein [43,44].…”
Section: Unikanie Apoptozymentioning
confidence: 99%
“…Szczegółowe poznanie ścieżek apoptotycznych i antyapoptotycznych oraz zrozumienie funkcji białek regulatorowych zaangażowanych w te szlaki pozwala na uwrażliwienie komórek nowotworowych na apoptozę, a tym samym poprawę skuteczności obecnych terapii. Możliwe jest to dzięki zewnątrzpochodnemu wywoła-niu apoptozy poprzez sygnalizację TRAIL lub zahamowanie antyapoptotycznej aktywności białka Bcl-2 lub białka IAP [43,44].…”
Section: The Ability To Invade and Form Metastasesunclassified
“…Drugs approved for clinical use as well as many in the development pipeline aim to alter apoptotic signalling outcome or to trigger initiation of apoptosis, for example SMAC mimetics or BH3 mimetic Venetoclax respectively. However, these approaches have not been without their complications with both ontarget and off-target dose limiting toxicity reported, as well as the development of drug-induced resistance (reviewed in [2]). Despite the exciting progress that has been made in understanding and targeting the complex pathways that commits a cell to die by apoptosis, it is becoming increasingly clear that simply characterising the effector pathways is not enough [2].…”
Section: Commentarymentioning
confidence: 99%
“…However, these approaches have not been without their complications with both ontarget and off-target dose limiting toxicity reported, as well as the development of drug-induced resistance (reviewed in [2]). Despite the exciting progress that has been made in understanding and targeting the complex pathways that commits a cell to die by apoptosis, it is becoming increasingly clear that simply characterising the effector pathways is not enough [2]. Understanding the regulatory pathways and checkpoints at the crucial commitment points that trigger these executioner cell death pathways is equally important and could be the key to enable successful modulation of death pathways that determine cell fate.…”
Section: Commentarymentioning
confidence: 99%